Correlation of Psoas Muscle Index with Fragility Vertebral Fracture: A Retrospective Cross-Sectional Study of Middle-Aged and Elderly Women - Yihui Zhang; Yilihamu Dilixiati; Wei Jiang; Xiufeng Cao; Yuanyuan Chen; Hui Guo (International Journal of Endocrinology)
Objective. To investigate the correlation of psoas muscle index (PMI) with fragility vertebral fracture. Methods. A total of 184 middle-aged and elderly women were included in the study. We measured the bilateral psoas muscle area on the picture archiving and communication system (PACS) from computed tomography images and calculated PMI. We observed lateral radiographs of the thoracolumbar spine and assessed vertebral fractures using the Genant semiquantitative method. The T-score, bone mineral density (BMD) of the lumbar (L)1-4, femoral neck, and trochanter were measured by dual-energyX-ray absorptiometry (DXA). The data was collected and then statistically analyzed. Results. The PMI of the nonosteoporosis group was higher than that of the osteoporosis group (P value = 0.006). Height in the nonosteoporosis group was higher than that in the osteoporosis group (P value = 0.013). Weight, body mass index (BMI), left psoas muscle area, BMD of the L1-4, femoral neck, femoral trochanter, and T-score in the nonosteoporosis group were higher than those in the osteoporosis group (P value <0.001). The right psoas muscle area in the nonosteoporosis group was higher than that in the osteoporosis group (P value = 0.008). The incidence of combined thoracolumbar fracture was significantly higher in the osteoporosis group than that in the nonosteoporosis group (P value <0.001). For nonosteoporosis subjects, the PMI of the vertebral fracture group was lower than that of the nonvertebral fracture group (P value = 0.034). Conclusions. A decrease in height, weight, BMI, bilateral psoas muscle area, and PMI is associated with osteoporosis. Combined thoracolumbar fractures are more common in osteoporosis. Sarcopenia may be an independent risk factor for nonosteoporotic vertebral fractures.